2023
DOI: 10.3390/agriculture13071424
|View full text |Cite
|
Sign up to set email alerts
|

Current Applications and Trends in Rabbit Nutraceuticals

Abstract: To ensure the sustainability of rabbit production and protect the global rabbit industry, cost-effective and practical strategies for improving rabbit production and meat quality must be developed. Recently, rabbit farming, like other animal farming, has faced feed shortages due to the impact of climate change, high competition among livestock species, and war conditions. The continued use of conventional feed additives in rabbit diets, whether derived from plant or animal sources, has become a critical issue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 141 publications
0
14
0
Order By: Relevance
“…Many natural substances produced by honeybees, such as propolis, royal jelly, beeswax, venom, slum gum, and pollen have unique structures and high nutritional value with a variety of medicinal qualities [28]. Despite some of these substances being considered by-products, they are sources of bioactive compounds with relevant biological effects and significant impacts on animal physiological and productive performance [4,29,30]. Several studies have found that bee products, with a high content of essential amino acids, antioxidants, active enzymes, vitamins, minerals, antibacterial, antiprotozoal, and immunostimulant substances, can improve animals' growth, meat quality, and immunological performance [3,4,[31][32][33][34] (Figure 1).…”
Section: Propolismentioning
confidence: 99%
See 4 more Smart Citations
“…Many natural substances produced by honeybees, such as propolis, royal jelly, beeswax, venom, slum gum, and pollen have unique structures and high nutritional value with a variety of medicinal qualities [28]. Despite some of these substances being considered by-products, they are sources of bioactive compounds with relevant biological effects and significant impacts on animal physiological and productive performance [4,29,30]. Several studies have found that bee products, with a high content of essential amino acids, antioxidants, active enzymes, vitamins, minerals, antibacterial, antiprotozoal, and immunostimulant substances, can improve animals' growth, meat quality, and immunological performance [3,4,[31][32][33][34] (Figure 1).…”
Section: Propolismentioning
confidence: 99%
“…However, poultry and rabbit industries have recently experienced numerous challenges, including climate change, disease spread, and antibiotic misuse. Antibiotics have been widely used in poultry and rabbit farms for decades to increase animal productive traits [2][3][4][5]. Overuse of antibiotics as growth promoters in poultry and rabbit farms has resulted in several adverse effects, including the development of microbial resistance and transference [5][6][7], and the residues remaining in the consumed product.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations